Peran Tenaga Kerja dan Teknologi dalam Meningkatkan Produktivitas Perkebunan Karet di Provinsi Lampung - Raihan Sadad; Erlin Kurniati (SUAN PUBLISHER, 2025)
This study aims to examine the role of Labor and technology in increasing the productivity of rubber plantations in Lampung Province with a qualitative approach. Rubber plantations in Lampung have an important contribution to the local economy, but their productivity is still influenced by factors such as labor quality and technology adoption. This study uses in-depth interviews and direct observation of rubber farmers, plantation managers, and agricultural experts to gain a deeper understanding of the challenges and opportunities. The results showed that a trained and competent workforce greatly affects the efficiency of the rubber production process, while technology, such as the use of modern harvesting tools and more efficient cultivation methods, can increase production yields. However, limited access to the latest technology and low levels of training are major barriers to improving productivity. Therefore, this study recommends the need for increased workforce training as well as expanded access to appropriate technologies to improve the sustainability and competitiveness of rubber plantations in Lampung Province.